DLX5 promotes Col10a1 expression and chondrocyte hypertrophy and is involved in osteoarthritis progression - Jinnan Chen; Fangzhou Chen; Xuan Wu; Huiqin Bian; Chen Chen; Xiaojing Zhang; Ruoxuan Hei; XiaotongYang; Haochun Yuan; Qian Wang; Yaojuan Lu; Longwei Qiao; et al. (Genes and Diseases, 2023)
Osteoarthritis (OA) has been considered non-reversible as articular cartilage wears down with limited repair capacity. Enhanced chondrocyte hypertrophy and increased type X collagen gene (COL10A1) expression have been associated with OA. Therefore, regulators controlling collagen X expression and chondrocyte hypertrophy may play a role in OA intervention. Here, we investigated how Distal-less homeobox 5 (DLX5), the distal-less homeobox family member, controls murine Col10a1 gene expression and chondrocyte hypertrophy in chondrogenic cell models and its role in a murine OA model. Through qRT-PCR and Western blot analyses, we detected significantly increased levels of COL10A1 and DLX5 in hypertrophic MCT and ATDC5 cells compared to their proliferative stage. Forced expression of Dlx5 further increases, while knockdown of Dlx5 decreases COL10A1 expression in hypertrophic MCT cells. We have performed dual-luciferase reporter and ChIP assays and demonstrated that DLX5 promotes reporter activity through direct interaction with Col10a1 cis-enhancer. We established a murine OA model and detected markedly increased COL10A1 and DLX5 in the articular cartilage and subchondral bone of the OA mice compared with the controls. Notably, forced overexpression of DLX5 in hypertrophic MCT cells up-regulates RUNX2, and adjacent DLX5 and RUNX2 binding sites have previously been found within the Col10a1 cis-enhancer. Together, our data suggest that DLX5 may cooperate with RUNX2 to control cell-specific Col10a1 expression and chondrocyte hypertrophy and is involved in OA pathogenesis.